PELAKSANAAN RPP PADA PEMBELAJARAN IPS DI SMP NEGERI 13 PONTIANAK - Ulvia Desmadita; Aminuyati Aminuyati; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to determine the suitability of the Lesson Plan (RPP) with the learning implementation of Social Studies teacher of SMP Negeri 13 Pontianak in class VIII A, VIII B, and VIII C. This research was conducted from April to May 2019. The method of this research was the qualitative descriptive method. The techniques of this research were observation, interview, and documentation. The result of the research on the first problem showed that in the implementation of the lesson plan with learning, it was carried out with the percentage of 86.6%, it categorized as very good. While the second problem regarding to the components of the Lesson Plan made by the teacher which consists of 13 components was very good, based on the Curriculum 2013 that applied, with the percentage of 85%, and the result of the third research problem about constraints experienced in the implementation of the lesson plan in learning Social Studies to the eighth grade of SMP Negeri 13 Pontianak related to facilities and infrastructures, improper of the time allocation, the different characteristics of students and schools, and the certain other unexpected conditions. Keywords: Analysis, Implementation of Lesson Plan (RPP), Social Studies (IPS).